Trade Less and Exit Overcrowded Markets: Lessons from International Mutual Funds. (30th July 2019) - Dyakov, Teodor; Jiang, Hao; Verbeek, Marno
Abstract: We study active investment skills in relation to returns to scale in the active mutual fund industry. Using a sample of 13, 807 funds from sixteen domicile countries investing in forty-two equity markets from 2001 to 2014, we find that they achieve negative trading performance on average, driven mainly by particularly low returns to their trades in US equities. Exploring their investment environment, we find convincing evidence of decreasing returns to scale around the world, especially for the US market. Based on theory of optimal fund size, we estimate the optimal size of the active mutual fund industry. We find that the active mutual fund industry in USA has exceeded the optimal level, whereas in the international markets, there may still be room for further expansion. Consistent with this view, we find that mutual fund managers have been gradually reallocating their assets away from the USA and more into international equity markets.